Symbolic Code of S/Z: A Semiological Reading of James Joyces Two Gallants - Booryazadeh, Seyed Ali; Faghfori, Sohila; Zohdi, Esmaeil (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Like a number of other stories of Dubliners,Two Gallants because of it coded polyphony is debatable on the level of significance. It seems that the story strategically convey some crucial information to the reader by deciphering its symbolic codes. Accordingly, this study in accord with Roland Barthes semiology and specified codes in S/Z makes an attempt to explicate the symbolic codes and structural components that carry an invisible message of James Joycs Two Gallants.